SOCIAL LISTENING ANALYSIS OF JUMBO MOVIE ON SOCIAL MEDIA: REPRESENTATIONS OF SUPERNATURAL ELEMENTS AND POWER RELATIONS - Wicaksono, Yudi Krisno; Mustofa, Ilham; Bachtiar, Rizqi; Sari, Ima Frafika; Zuhri, Saefudin (Universitas Padjadjaran, 2025)
Public reception of the Indonesian animated film Jumbo was analyzed through social listening to explore supernatural elements and socio-political power relations. This study aimed to examine audience perceptions of supernatural motifs, identify interpretations of power dynamics, and generate insights into digital film reception using a mixed-methods sequential explanatory design (Creswell & Plano Clark). Primary data consisted of publicly available organic conversations from 2,700 unique authors across X (Twitter), TikTok, Instagram, YouTube, Facebook, and blogs. Data were collected via Talkwalker using Boolean queries that combined the keyword “Jumbo Movie” with terms related to supernatural elements and power relations. The data collection period spanned from 28 April to 5 May 2025, resulting in a dataset of 201,000 mentions and 309,500 engagements. Quantitative analysis generated sentiment polarity, emotion distribution, and topic clusters. These results were subsequently interpreted qualitatively using Barthesian semiotics and Foucault–Gramsci power theory, and validated through cross-platform triangulation and a 10 percent manual review. The findings indicate that discussions were predominantly neutral (69.1%), followed by positive (27.4%) and negative (3.6%) sentiments. The character Meri is interpreted as a local cultural symbol and an agent of change embodying alternative spiritual power. This study concludes that social listening effectively bridges computational patterns with critical cultural analysis, positioning Jumbo as a cultural text that articulates identity and resistance in digital Indonesia. Comparative applications of this analytical protocol are recommended for other Indonesian films.